2019
DOI: 10.1186/s12953-019-0149-9
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic protein Carbonylation profiles induced by lipid accumulation and oxidative stress for investigating cellular response to non-alcoholic fatty liver disease in vitro

Abstract: Background Non-alcoholic fatty liver disease (NAFLD) is caused by excessive accumulation of fat within the liver, leading to further severe conditions such as non-alcoholic steatohepatitis (NASH). Progression of healthy liver to steatosis and NASH is not yet fully understood in terms of process and response. Hepatic oxidative stress is believed to be one of the factors driving steatosis to NASH. Oxidative protein modification is the major cause of protein functional impairment in which alteration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 42 publications
2
7
0
Order By: Relevance
“…Second, FA treatment significantly suppressed redundant lipid deposition in the liver, which is consistent with previous studies ( Ma et al, 2019 ). Lipid accumulation in hepatocytes causes lipid peroxidation and increases oxidative stress ( Chienwichai et al, 2019 ), which is an important mechanism in liver injury ( Li et al, 2015 ; Dey et al, 2020 ). The antioxidant effect of FA has also been identified in other studies ( Bumrungpert et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Second, FA treatment significantly suppressed redundant lipid deposition in the liver, which is consistent with previous studies ( Ma et al, 2019 ). Lipid accumulation in hepatocytes causes lipid peroxidation and increases oxidative stress ( Chienwichai et al, 2019 ), which is an important mechanism in liver injury ( Li et al, 2015 ; Dey et al, 2020 ). The antioxidant effect of FA has also been identified in other studies ( Bumrungpert et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies in rats or mice have proved the intensified oxidation of lipids, which was assessed based on the level of TBARS, after the administration of ethanol at a concentration of 18-30% [36][37][38][39][40][41], but they also showed an increased level of protein carbonyl groups in the liver as a result of the intensification of oxidative stress by ethanol consumption [40][41][42]. According to some authors, the process of protein oxidation may be of great importance in the pathogenesis of ALD [41], as well as in the pathogenesis of the non-alcoholic fatty liver disease (NAFLD), including non-alcoholic steato-hepatitis (NASH) [43]. In the present study, the highest level of protein carbonyl groups observed in the liver was attributed to beer consumption, which may once again suggest the adverse effect of some components present in beer, or the higher vulnerability of growing organisms to those components.…”
Section: Discussionmentioning
confidence: 99%
“…The subsequent oxidative stress not only causes cell damage but also contributes lipids and proteins oxidation, including protein carbonylation. Alter of protein carbonyl formation correlated with free radicals production within HepG2 cells (Chienwichai, et al, 2019).…”
Section: Discussionmentioning
confidence: 88%